Antioxidant Capacity of Equisetum telmateia and Urtica dioica: Secondary Benefits in Renal Health Beyond Crystal Inhibition - Tajdida Magayr; Shamsi Saad; Fatima Abdulsalam (AlQalam Journal of Medical and Applied Sciences, 2025)
Kidney stone disease is a common condition characterized by the formation of crystalline deposits in the kidneys, with calcium oxalate being the primary component of most stones. Oxidative stress plays a significant role in the pathogenesis of kidney stones by promoting inflammation, lipid peroxidation, and renal damage. While current treatments mainly focus on inhibiting crystal formation, there is limited attention given to addressing oxidative stress. This study evaluates the antioxidant capacity of Equisetum telmateia (Giant Horsetail) and Urtica dioica (Nettle) and explores their potential to reduce oxidative stress in renal health. Phytochemical analysis of both plants revealed the presence of key bioactive compounds, including phenolic acids, flavonoids, and fatty acid derivatives, which are known for their antioxidant properties. In vitro assays, including ABTS and DPPH, demonstrated significant radical scavenging activity for both plant extracts, with E. telmateia showing slightly higher inhibition at 500 µg/mL compared to U. dioica. Cytotoxicity testing on zebrafish embryos and Vero cells revealed no significant toxicity at therapeutic doses, confirming the safety of both extracts. These findings suggest that E. telmateia and U. dioica not only possess potent antioxidant activity but may also protect renal tissues from oxidative damage associated with kidney stone formation. The study highlights the therapeutic potential of these plants in kidney stone prevention and management, providing a holistic approach by targeting both crystallization and oxidative stress. Further clinical research is warranted to explore the efficacy of these plants in human kidney stone disease management.